2007
DOI: 10.1097/fjc.0b013e3181583d80
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite is Involved in the Dysfunction of Vasorelaxation in SHR/NDmcr-cp Rats, Spontaneously Hypertensive Obese Rats

Abstract: SHR/NDmcr-cp (SHR-cp) rats display typical symptoms and features of the metabolic syndrome. We previously reported that endothelium-dependent relaxation decreases in the thoracic aortas of SHR-cp rats, despite increased nitric oxide (NO) production from the endothelium. In the present study, to search for the reasons for this contradiction, we investigated whether vascular abnormality could be reduced by treatment of SHR-cp rats with antihypertensive drugs; a calcium channel blocker (amlodipine), an alpha 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…13 Almost all experimental models of hypertension display some form of oxidative excess. [14][15][16][17][18][19][20] As inhibition of ROS-generating enzymes, anti-oxidants and ROS scavengers reduce blood pressure, whereas pro-oxidants increase blood pressure, it has been suggested that ROS are causally associated with hypertension, at least in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…13 Almost all experimental models of hypertension display some form of oxidative excess. [14][15][16][17][18][19][20] As inhibition of ROS-generating enzymes, anti-oxidants and ROS scavengers reduce blood pressure, whereas pro-oxidants increase blood pressure, it has been suggested that ROS are causally associated with hypertension, at least in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental models of hypertension exhibit some degree of oxidative stress (48,67,93,95,236). Moreover, mice with reduced antioxidant enzyme systems and those deficient in NADPH oxidase have higher blood pressures than those with intact systems.…”
Section: Introductionmentioning
confidence: 99%
“…Similar brachial BP and CAP reductions were achieved with valsartan plus HCTZ versus amlodipine; however, valsartan plus HCTZ provided a greater reduction in arterial stiffness (estimated by aortic PWV) [97]. Reductions in central SBP were greater with fosinopril plus HCTZ than with indapamide or amlodipine; this correlated with 24-hour and nighttime SBP reductions, but not with seated cuff SBP [98].…”
Section: Capmentioning
confidence: 55%